Upaya Meningkatkan Kemampuan Berbahasa Melalui Metode Bercerita Dengan Media Ritatoon Di Paud Qaireen T.A 2022/2023 - Khairani Khairani; Rahmadi Ali; Juli Yanti Harahap (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine how to improve children's language skills through storytelling methods with ritatoon media for children aged 5-6 years at Qaireen PAUD. This research is a classroom action research (PTK) that uses the Kemmis and Mc Tanggart model. The subjects of this study were 20 children, consisting of 10 boys and 10 girls. Data collection techniques used in this study were observation of improving children's language skills through storytelling methods with ritatoon media, teacher and child activities and documentation. The data analysis technique used in this research is descriptive qualitative. Based on the results of the study, it is known that there is an increase in children's language skills through storytelling methods with ritatoon media. This is known from the average child who gets the level of achievement of children developing as expected (BSH) and developing very well (BSB) in the Pre-Cycle with an average percentage of 8.75%, then in Cycle I the level of achievement of children developing as expected (BSH) and developing very well (BSB) with an average percentage of 53.75%, so we can see an increase in Pre-cycle to Cycle I by (45%) However, in cycle I it has not developed well so it is continued to Cycle II. The level of achievement of children developing as expected (BSH) and developing very well (BSB) Cycle II with an average percentage of 95%. Based on the results of the study it can be concluded that ritatoon media can improve the language skills of children aged 5-6 years. The increase occurred, because in telling stories using ritatoon which had not previously been applied in the school, big ritatoon special characteristics are colorful, interesting pictures, as well as words that can be repeated, have predictable properties, and are fun.